Si-Miao-Yong-An (SMYA) Decoction May Protect the Renal Function Through Regulating the Autophagy-Mediated Degradation of Ubiquitinated Protein in an Atherosclerosis Model - Zhu, Ze-Bing; Song, Ke; Huang, Wei-Jun; Li, Hui; Yang, Hui; Bai, Yun-Qi; Guo, Ke-Ting; Yang, Rui-Bing; Lou, Wen-Jiao; Xia, Chen-Hui; Nie, Bo; Liu, Wei-Jing (Frontiers in Pharmacology, 2020)
Hyperlipidemia is common and its renal toxicity has attracted a great attention. Si-miao-yong-an (SMYA) is a famous ancient decoction of traditional Chinese medicine (TCM), which is still widely used in clinical treatment. In this study, we observed and explored its efficacy and mechanism in protecting renal function in an atherosclerosis model. The results showed that the serum, Cr urinal KIM-1 and NGAL were significantly decreased in SMYA group. Although SMYA failed to alleviate the lipid accumulation, or decreased p-NFκB, or increase SOD in kidney tissue, the level of ubiquitinated protein and P62 were decreased in SMYA group. What’s more, higher LC3Ⅱ level was observed in SMYA group. In conclusion, these data indicated that SMYA decoction may protect renal function in hyperlipidemia via regulating the autophagy-mediated degradation of ubiquitinated protein.